(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
The industrialization of agriculture has favoured the use of plenty of agrochemicals including fertilizers, pesticides, micronutrients. Consumption of pesticides has become an integral part of modern agriculture and is an effective and economical way to enhance the yield quality and quantity. Approximately, 2 million metric tons (MT) of pesticides are utilized annually worldwide. India stands 12th in pesticide use globally and 3rd in Asia after China. India shares only 1% of the global pesticide use. After the green revolution, there is increased use of chemical pesticides which resulted in contaminating the environment and the long-term implications on the society. Indiscriminate and excessive application of pesticides not only have damaged the environment but also have entered the food chain thereby affecting health and development. However, the role of pesticides in augmenting agricultural output has been well perceived and these have been considered as essential inputs in agricultural production. The present paper aimed to study the consumption pattern of pesticides and fertilizers among the small and marginal farmers. This study also aimed to know the farmers’ knowledge about the safe handling and application of pesticides and their practices on pesticide usage. While doing so, it highlights some issues like change in the cropping pattern among small and marginal farmers and also emphasizes on soil degradation and environmental issues.